Factors Controlling Storage, Sources, and Diagenetic State of Organic Carbon in a Prograding Subaerial Delta: Wax Lake Delta, Louisiana. Issue 5 (3rd May 2019) - Shields, Michael R.; Bianchi, Thomas S.; Kolker, Alexander S.; Kenney, William F.; Mohrig, David; Osborne, Todd Z.; Curtis, Jason H.
Abstract: Wax Lake Delta, southern Louisiana, is a coastal delta that formed following the dredging of a river channel in 1941 and is a field model for investigating the geomorphology, ecology, carbon dynamics, and carbon storage capacity in young prograding deltas. However, it is unknown how the transition from subaqueous to subaerial sediments affects the sources and quality of the sequestered carbon. We investigated these variations within the sediments of Wax Lake Delta using amino acid, lignin, and stable carbon isotope compositions of the organic matter (OM). A principal component analysis of these proxies highlighted variability in organic carbon (OC) composition with changes in elevation. The transition from subaqueous to subaerial sediments at 0‐cm mean lower low water is an important component of the OM composition. In addition to the changes observed for OM source and quality, the OC loadings (OC/SA; mg C/m 2 ) also increase as the delta aggrades and accumulates sediments with loadings typical of delta topsets and mobile mud banks (OC/SA < 0.4) to riverine sediments (0.5 < OC/SA < 1) and eventually to highly productive regions (OC/SA > 1). Linking this multiproxy approach with environmental variables such as elevation provides a path for incorporating OM dynamics into geomorphic models. Key Points: A multibiomarker approach characterizes the sources and diagenetic state of organic matter in Wax Lake Delta sediments Changes in the source and diagenetic state of organic matter in Wax Lake Delta sediments are correlated with elevation The OC/SA loadings increase as the delta aggrades, resulting in a semilog relationship between TOC and silt + clay content